2002
DOI: 10.1093/glycob/12.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Specific effects of fructo- and gluco-oligosaccharides in the preservation of liposomes during drying

Abstract: The fructan family of oligo- and polysaccharides is a group of molecules that have long been implicated as protective agents in the drought and freezing tolerance of many plant species. However, it has been unclear whether fructans have properties that make them better protectants for cellular structures than other sugars. We compared the effects of fructans and glucans on membrane stability during air-drying. Although glucans of increasing chain length were progressively less able to stabilize liposomes again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
147
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 29 publications
19
147
0
4
Order By: Relevance
“…Recent in vitro studies have provided direct evidence that both RFOs and fructans may be involved in cell membrane stabilization (Hincha et al, 2002Vereyken et al, 2003). In vivo studies showed that down-regulation of a-Gal activities resulted in both enhanced raffinose content and freezing tolerance in transgenic petunia (Petunia hybrida; Pennycooke et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro studies have provided direct evidence that both RFOs and fructans may be involved in cell membrane stabilization (Hincha et al, 2002Vereyken et al, 2003). In vivo studies showed that down-regulation of a-Gal activities resulted in both enhanced raffinose content and freezing tolerance in transgenic petunia (Petunia hybrida; Pennycooke et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in leaf tissue reduces total plant water loss (Gepstein, 2004;Munne Bosch and Alegre, 2004). A minimum water supply to the meristematic tissues is maintained (Karcher et al, 2008;McWilliam and Kramer, 1968;Volaire and Lelievre, 2001), and high concentrations of fructans and dehydrins contribute to osmoregulation and membrane stabilisation of these tissues (Hincha et al, 2000(Hincha et al, , 2002. High carbohydrate reserves are associated with superior plant resilience and recovery after severe drought (Boschma et al, 2003).…”
Section: Breeding For the Future Climatementioning
confidence: 99%
“…Liposome destabilization leads to leakage of the dye into the surrounding medium, where it is diluted sufficiently to allow fluorescence emission. CF leakage was determined with a Fluoroscan Ascent fluorescence plate reader (excitation wavelength of 444 nm and emission wavelength of 555 nm; Labsystems) before and after liposome disruption by the addition of Triton X-100 (Hincha et al, 2002).…”
Section: Cf Leakage and Liposome Fusion Experimentsmentioning
confidence: 99%